Raising the bar on fibrinogen: a retrospective assessment of critical hypofibrinogenemia in severely injured trauma patients - Justin Richards; Thomas Scalea; Jonathan H Chow; Rosemary Kozar; Benjamin T Fedeles (Trauma Surgery & Acute Care Open, 2023)
Objectives Fibrinogen depletion may occur at higher levels than historically referenced. We evaluated hypofibrinogenemia and associated mortality and multiple organ failure (MOF) after severe injury.Methods Retrospective investigation including 417 adult patients with Injury Severity Score (ISS) >15. Demographics and injury characteristics were collected. Fibrinogen within 30 minutes of admission was described: <150 mg/dL, 150 mg/dL to 200 mg/dL and >200 mg/dL. Primary outcome: 28-day mortality. Secondary outcomes: 28-day MOF and blood product transfusion. Multivariable logistic regression model evaluated association of fibrinogen categories on risk of death, after controlling for confounding variables. Results presented as OR and 95% CIs.Results Fibrinogen <150 mg/dL: 4.8%, 150 mg/dL to 200 mg/dL: 18.2%, >200 mg/dL: 77.0%. 28-day mortality: 15.6%. Patients with <150 mg/dL fibrinogen had over fourfold increased 28-day mortality risk (OR: 4.9, 95% CI 1.53 to 15.7) after adjusting for age, ISS and admission Glasgow Coma Scale. Patients with lower fibrinogen were more likely to develop MOF (p=0.04) and receive larger red blood cell transfusion volumes at 3 hours and 24 hours (p<0.01).Conclusions Fibrinogen <150 mg/dL is significantly associated with increased 28-day mortality. Patients with fibrinogen <150 mg/dL were more likely to develop MOF and required increased administration of blood products. The optimal threshold for critically low fibrinogen, the association with MOF and subsequent fibrinogen replacement requires further investigation.Level of evidence Level III